Correlation of the intestinal flora and its metabolites with the colonic transport function in functional constipation - Hu, Lunan; Liu, Qihong; Ke, Xiao; Zhao, Peilin; Fang, Wenyi; Ren, Yan (Frontiers in Microbiology, 2025)
BackgroundFunctional constipation (FC) is a clinically frequent intestinal disorder. A growing body of evidence emphasizes the link between intestinal microecological imbalance and constipation. However, the microbiota composition associated with FC and the mechanisms by which metabolites influence gut motility remain poorly understood.MethodsStool samples were collected from 60 participants (20 FC patients with delayed colonic transit time, 20 FC patients with normal colonic transit time, and 20 healthy controls), and macrogenomics and metabolomics were used to assess the differences in the microbiota and metabolite composition of different colonic transit functions in FC. In addition to assessing clinical symptoms, this study aimed to better understand how intestinal flora contributed to impaired gut motility in FC patients.ResultsSignificant microbiota taxonomic differences were observed across different gut dynamics in FC; Alistipes, Akkermansia, Oscillibacter, Ruthenibacterium, Alistipes_onderdonkii, and Ruthenibacterium_lactatiformans were key bacteria in FC patients with delayed colonic transit time; Roseburia and Klebsiella_pneumoniae were key bacteria in FC patients with normal colonic transit time; and Escherichia, Enterobacter, Escherichia_coli, Ruminococcus gnavus, Enterobacter_cloacae_complex, and Megamonas_funiformis were the key organisms in healthy controls. The metabolomics analysis revealed three differentially abundant short-chain fatty acids: acetic acid, propionic acid, and butyric acid. Furthermore, there were 11 differentially abundant bile acids, including β-muricholic acid and nor-deoxycholic acid. Correlation analysis revealed significant correlations between the 14 differential bacteria and the 14 metabolites, Notably, Roseburia was positively correlated with butyrate and acetate levels (FDR < 0.05). In addition, Oscillibacter showed positive correlations with several BAs, including nor-deoxycholic acid, isoallolithocholic acid, α-muricholic acid, β-muricholic acid, 5α-cholanic acid-3α-ol, and dehydrolithocholic acid (FDR < 0.05). The Spearman’s |r |value >0.6 combination in the correlation analysis between fecal differential bacteria and differentially abundant metabolites revealed an AUC value of 0.854 between FC patients and healthy controls, indicating good predictive ability.ConclusionThe identified differences in the composition and metabolites of different colonic transmission-dynamic microbiota in FC further our understanding of the underlying mechanisms involved in FC pathogenesis and may provide new insights into diagnostics and therapeutic interventions.